Nature School Curriculum Model: Study of curriculum development at Al Izzah Nature School Sidoarjo - Hosna, Rofiatul; Karimah, Ghunniyatul (Tribakti: Jurnal Pemikiran Keislaman, 2020)
Schools are a strategic tool for building the next generation of the nation, the main focus is character education. Strengthening moral education or character education in the current context is very relevant to overcoming the moral crisis that is happening in our country. Of course these goals can be effective if the child is not only stuffed with lessons like in ordinary schools, but also concrete objects are introduced. So that understanding is more complete. Therefore, the School of Nature is present amid the decline in the quality of education in Indonesia, which is a relic of the Netherlands and Japan. The purpose of this study was to determine the curriculum model, the curriculum development process and the factors that support and inhibit the curriculum development process at the Al-Izzah Nature School Sidoarjo. The method I use in this research is descriptive qualitative method. Data collection techniques used in this study are documentation, namely by gathering information from research in the field related to the topic and analyzing it. The results of the analysis concluded that the curriculum model used in the Al-Izzah Nature School Sidoarjo Elementary School was a Humanistic curriculum, with the curriculum development process being the Grass Roots model and the interpersonal relationship model. And the supporting factors in the curriculum development process are. And the factors which become obstacles in the curriculum development process are the facilities used in out bond or camping activities are not yet available.